THE DESCRIPTION MODEL OF INFORMATION CULTURE TOURISM BACHELORS’ FORMATION IN TRAINING PROCESS - Zubekhina, Tatiana V. (Educological discourse, 2014)
The theoretical model of information culture Tourism Bachelors' formation in professional training process; the approaches and principles of information culture Tourism Bachelors’ formation are substantiate in this article. Also the forms and methods, organizational, logical, technological stages are proposed.